A measurement of illumination variation-resistant noncontact heart rate based on the combination of singular spectrum analysis and sub-band method. (March 2021) - Ryu, JongSong; Hong, SunChol; Liang, Shili; Pak, SinIl; Chen, Qingyue; Yan, Shifeng
Highlights: A Measurement of Illumination Variation-Resistant Noncontact Heart Rate Based on the Combination of Singular Spectrum Analysis and Sub-band Method JongSong Ryu, SunChol Hong, Shili Liang, SinIl Pak, Qingyue Chen, Shifeng Yan Extraction of illumination variation directly from facial ROI using singular spectrum analysis (SSA) Modification of the previous POS method by changing the axis of projection A novel method which is more robust to the interference of illumination variance based on the combination of SSA and the modified POS method Confirmation of the performance of the proposed method through the experiment based on the public database and the self-collected database Abstract: Background and Objective: The imaging photoplethysmography method is a non-contact and non-invasive measurement method that usually uses surrounding illumination as an illuminant, which can be easily influenced by the surrounding illumination variations. Thus, it has a practical value to develop an efficient method of heart rate measurement that can remove the interference of illumination variations robustly. Method: We propose a novel framework of heart rate measurement that is robust to illumination variations by combining singular spectrum analysis and sub-band method. At first, we extract the blood volume pulse signal by applying the modified sub-band method to the raw facial RGB trace signals. Then the spectra for the interference of illumination variations are extracted from the raw signal obtained from facial regions of interest by using singular spectrum analysis. Finally, we estimate the more robust heart rate through comparison analysis between the spectra of the extracted blood volume pulse signal and the illumination variations. Results: We compared our method with several state-of-the-art methods through the analysis using the self-collected data and the UBFC-RPPG database. Bland-Altman plots and Pearson correlation coefficients pointed out that the proposed method could measure the heart rate more accurately than the state-of-the-art methods. For the self-collected data and the UBFC-RPPG database, Bland-Altman plots showed that proposed method caused better agreement with 95% limits from -4 bpm to 10 bpm and from -2 bpm to 4 bpm respectively than the other state-of-the-art methods. It also revealed that the highly linear relation was held between the estimated heart rate and ground truth with the correlation coefficients of 0.89 and 0.99, respectively. Conclusion: By extracting illumination variation directly from the facial region of interest rather than from the background region of interest, the proposed method demonstrates that it can overcome the drawbacks of the previous methods due to the illumination variation difference between the background and facial regions of interest. It can be found that the proposed method has a relatively good robustness regardless of whether illumination variation exists or not.